PENGKAJIAN UJI ADAPTASI VARIETAS PADI UNGGUL BARU DI KABUPATEN TAPANULI SELATAN SUMATERA UTARA (Talenta Publisher, 2015)
Study of six high yielding varieties of rice adaptation performed on wetland rice fields in the North of Sumatera.The activities focus on location in Pintu Padang I village. The objective is to implement mentoring activities rice technology through the test and open-field VUB adaptation to increase rice production. The team have been mentoring technology of SL-PTT-Rice in West Tapanuli Regency, as has been done in 2013. Mentoring of the application of technological innovation with approaches Integrated Crop Management (PTT). The test of adaptation to six varieties (Inpari 3, Inpari 10, Inpari 14, Inpari 15, Inpari 16 dan Mekongga). Through this activity, carried rice varieties test an acre in one location. The technologies presented are: new varieties, cropping patterns legowo 4:1, fertilizing, pest control, etc.. The test of adaptation to six varieties, the highest result was Mekongga (8,2 t/ha), Inpari 14 (8,1 t/ha) and Inpari 15 (8,1 t/ha)., so these varieties is very potential to be developed of the farmer and stakeholders.